Analisis Penyebab Kerusakan Unit Pompa Pendingin AC dan Kompresor menggunakan Metode FMEA - Muhammad Bob Anthony (Jurnal Teknologi, 2021)
PT. XYZ is a company engaged in the steel industry which produces steel slabs, steel billets, steel plates and steel wires. One of the equipment that often gets damaged is the air conditioning pump and compressor unit in the fluid center service. The results of the availability of the AC and compressor refrigeration pump units show that the availability value is still below  the company standards set so that an analysis of the root causes of the problem is needed and finding the best solution to fix existing problems by applying the failure mode and effect analysis (FMEA) method. FMEA is a method that systematically and structurally can analyze and identify the consequences of system and process failures and reduce or analyze the chances of failure. The purpose of this study is to identify and analyze the level of damage and its causes by applying the FMEA method. Based on the Pareto diagram of the damage to the air conditioning pump and compressor engine unit, it was found that the highest frequency of damage was the power supply with a down time percentage of 32.4%. The results of FMEA analysis produce two components that have a very high RPN value which is categorized as potential severity, namely fuse as the first component with an RPN value of 378 and the second is a fuse holder with an RPN value of 252. These two components are the main priority for improvement in the pump engine unit air conditioners and compressors especially for the machine and human aspects.